(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
The DNA barcode of a species is expected to vary only 2-7%, among different varieties of the species. There are more than 4000 morphologically different varieties of roses that evolved due to the selection pressure of the aesthetic choices of humans. The extensive use of roses in decoration, bouquet, as well as in medicine and food also increase the value of their species identification from forensic trace samples. DNA barcoding-based identification of species is emerging as a robust forensic technique. Here we have determined the DNA barcode of a few prominent varieties of rose and estimated variation among them as well as their phylogenetic relationships. The rbcl gene does not vary significantly among these rose varieties, at most, it can identify the class/group of a rose variety.